VD_FINDINFO Arrêt / 2022 / 837 vom 18. Oktober 2022 - VD Tribunal cantonal (2022)
ASSISTANCE JUDICIAIRE, DEMI-RENTE, ÉVALUATION DE L'INVALIDITÉ, ADMISSION DE LA DEMANDE | 28 LAI, 29 LAI, 4 al. 1 LAI, 6 LPGA, 7 LPGA, 8 LPGA